Design and Implementation of Multi-Configuration Rolling Machine - Mustafa, F.F.; Al-Musawi, S.Q.; A. Mahdi, Hussain; Salloomi, K. N.; Reda, S.D.; Al-Ashaab, Ahmed; Al-Jumaily, Adel (Al-Khwarizmi Engineering Journal, 2024)
For decades, metal corrugated sheets have usually been manufactured using conventional roll-forming machines with lower and upper rollers or a die and a press as the main shaping elements. However, these machines and their related processes present economic disadvantages because of additional expenses required to improve and manage forming tools. To overcome these drawbacks, reconfigurable machines, such as dedicated and flexible manufacturing systems, were used as alternatives; they possess high flexibility for accomplishing forming processes. Reconfigurable machines are designed around a particular family of manufactured outcomes, allowing for high system flexibility. In light of the latest developments in reconfigurable machine design, this study proposes a new sheet metal forming roller called the discrete multi disk roller (MDR) as an alternative to the traditional roller design. Unlike existing processes, the MDR minimises production costs associated with material loss and effectively decreases forming errors. Furthermore, it utilises multi-disk as reconfigurable rollers. The technique and applicable procedure of the MDR are described, and wavy sheets with different dimensions and shapes are formed to verify the applicability of the reconfigurable roller, a critical component in the forming process. Thirteen parts with different configuration profiles were produced using the proposed MDR machine.